COMBINATION OF VISUAL METHODS AND CARTOGRAPHIC DATA FOR IMPROVING LANE-LEVEL NAVIGATION ACCURACY - Древич, Любомир (SWorldJournal, 2025)
The object of study is methods for ensuring high-precision lane-level navigation for autonomous vehicles in real road environments. The relevance of the work is due to the fact that at automation levels L4-L5, even an error of tens of centimeters can lead